Effect CeoNarcissim On Tax Avoidance With Institusional Ownership As A Moderating (Empirical Study of Financial Sector Companies Listed on the Indonesian Stock Exchange for the 2019-2022 Period) - Ahmad muhlis; Mira; Andi Arman (P3I UMSurabaya, 2024)
The aim of this research is to determine the influence of the independent variable CEO Narcism, the dependent variable tax avoidance and ownership as a moderating variable in measuring CEO Narcism in carrying out Tax Avoidance and whether these two variables can be strengthened or weakened by institutional ownership of financial sector companies listed on the Stock Exchange Indonesia. The research method used is a quantitative method. The population in this study are financial sector manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2022 period. The sample in this study used a purposive sampling technique, based on the specified criteria, a sample of 43 samples was obtained. The type of data used is secondary data in the form of the company's annual report. The data analysis technique used is analysis. The Data Analysis Method used in this research is: Descriptive Statistics, Classic Assumption Test, Multiple Linear Regression Analysis with Moderated Regression Analysis and hypothesis testing. The research results show that the results of data analysis show that CEO narcissism has no effect on tax avoidance. This means that CEOs who have low or high levels of narcissism have no effect on tax avoidance, because the government through the DJP has provided tax incentives through interest charges, utilization of fiscal loss compensation. to reduce the amount of tax burden borne by the company. And institutional ownership is not able to moderate CEO Narcissism towards Tax Avoidance. This means that even though the level of institutional ownership is high in the company, institutional ownership is still unable to moderate CEO Narcissism towards tax avoidance because the company is unable to practice tax avoidance even though it has low and high levels of narcissistic CEO characters